2012
DOI: 10.1063/1.4722350
|View full text |Cite
|
Sign up to set email alerts
|

A high-pressure far- and mid-infrared study of 1,1-diamino-2,2-dinitroethylene

Abstract: High pressure infrared (IR) measurements of the insensitive explosive, 1,1-diamino-2,2-dinitroethylene (DADNE or FOX-7), have been performed in the far- and mid-IR spectral regions up to ∼28 GPa using a synchrotron source. Petroleum jelly and KBr were employed as the pressurizing media for the far- and mid-IR experiments, respectively. In both experiments, IR spectra were collected at various pressures both in compression and decompression to determine reversibility under pressure cycling. There is evidence fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 17 publications
3
41
1
Order By: Relevance
“…This behavior was attributed to the strengthening of hydrogen bonding in FOX-7 under pressure. 18,22 As we have already mentioned, the experimental Raman spectra showed several changes around 2 GPa, which were attributed to changes in the molecular conformation. 18 The spectral changes at this pressure included occurrence of new peaks at 151 and 607 cm −1 and disappearance of a peak at 499 cm −1 .…”
Section: Hydrostatic Pressurementioning
confidence: 76%
“…This behavior was attributed to the strengthening of hydrogen bonding in FOX-7 under pressure. 18,22 As we have already mentioned, the experimental Raman spectra showed several changes around 2 GPa, which were attributed to changes in the molecular conformation. 18 The spectral changes at this pressure included occurrence of new peaks at 151 and 607 cm −1 and disappearance of a peak at 499 cm −1 .…”
Section: Hydrostatic Pressurementioning
confidence: 76%
“…The FOX-7 crystal appears golden yellow and has two-dimensional wave-shaped layers with extensive intermolecular hydrogen bonding within the layers and with weaker van der Waals interactions between the layers. 14,15 Stresses in the crystal are reduced by the relative movement of layers, and in this manner, the crystal is not sensitive to mechanical strain. 5 Compared to the presently most widely used and powerful explosives RDX and HMX, FOX-7 yields the same number of moles (0.0405) of gaseous product per gram of compound for the complete decomposia) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…However, they found that no lattice transformations could be observed up to 8 GPa under hydrostatic conditions. Recent experiments at different temperatures and pressures found three possible phase transitions (at 2 GPa, 5 GPa and above 10 GPa) in mid and far IR regions 11,12 . Pravica et al 11 reported the strengthening of the hydrogen bond and softening of NH 2 stretching frequencies at high pressure by using IR experiments.…”
mentioning
confidence: 99%
“…Starting from the synthesis of this compound in 1998 3 , several studies were carried out to investigate its structural properties from ambient 4 to extreme conditions [5][6][7][8] , its thermal behavior with decomposition mechanism 9,10 and vibrational spectroscopy (IR and Raman) at different pressures and temperatures 5,11,12 . Beeman and Ostrak 4 determined the crystal structure of FOX-7 to be monoclinic with the space group P2 1 /n, which contains four molecules (56 atoms) per unit cell.…”
mentioning
confidence: 99%